2017
DOI: 10.1590/s1984-29612017061
|View full text |Cite
|
Sign up to set email alerts
|

Growth, mortality and susceptibility of oyster Crassostrea spp. to Perkinsus spp. infection during on growing in northeast Brazil

Abstract: Crassostrea rhizophorae and C. gasar oysters are cultivated in the northeast region. Perkinsus parasites infect bivalves, and their effects on oysters from tropical regions are poorly understood. This study evaluated the impact of Perkinsus infection on the productive traits of native oysters. Oysters were sampled bimonthly during 7 months, from July 2010 to February 2011, to evaluate growth rate, mortality and shell color patterns (white and dark-gray) (n = 500), and to determine the prevalence and intensity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
(47 reference statements)
1
8
1
2
Order By: Relevance
“…In recent years, the prevalence of Perkinsus observed in oysters from different regions of the country has varied considerably and, although the value found in this study (8%) has been lower than that recorded in oysters from that same estuary in 2015 (17.3%) and in oysters from Carnaubeira River in Maranhão (10.6%), the same was higher than the values recorded in oysters from the estuaries of the Rivers Camurupim, in Piauí (5.3%) and Pacoti, in Ceará, in 2009and 2010. In other states of the northeastern region, the prevalence of Perkinsus recorded in the RFTM assays has been higher than the values mentioned above (Luz et al, 2018;Queiroga et al, 2015;Scardua et al, 2017;Silva et al, 2016). In the present study, the infection intensity ranged from very light to light (clams), very light to severe (oysters) and very light to moderate (mussels).…”
Section: Resultscontrasting
confidence: 65%
See 1 more Smart Citation
“…In recent years, the prevalence of Perkinsus observed in oysters from different regions of the country has varied considerably and, although the value found in this study (8%) has been lower than that recorded in oysters from that same estuary in 2015 (17.3%) and in oysters from Carnaubeira River in Maranhão (10.6%), the same was higher than the values recorded in oysters from the estuaries of the Rivers Camurupim, in Piauí (5.3%) and Pacoti, in Ceará, in 2009and 2010. In other states of the northeastern region, the prevalence of Perkinsus recorded in the RFTM assays has been higher than the values mentioned above (Luz et al, 2018;Queiroga et al, 2015;Scardua et al, 2017;Silva et al, 2016). In the present study, the infection intensity ranged from very light to light (clams), very light to severe (oysters) and very light to moderate (mussels).…”
Section: Resultscontrasting
confidence: 65%
“…Since then, other studies have reported the occurrence of Perkinsus sp. in oysters of the genus Crassostrea from several regions (Brandão et al, 2013;Luz et al, 2018;Scardua et al, 2017). It is worth noting the record, in 2016, of the species P. chesapeaki, detected for the first time in South America, infecting oysters from the Jaguaribe River estuary, Ceará (Dantas et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Two mangrove oyster species (Crassostrea rhizophorae and C. gasar) inhabit the estuaries of the Northeast region of Brazil (3) . The oyster C. rhizophorae is naturally found in estuarine environments along the Brazilian coast, fixed on substrates, mainly in the roots of mangroves (4) .…”
Section: Introductionmentioning
confidence: 99%
“…The oyster C. rhizophorae is naturally found in estuarine environments along the Brazilian coast, fixed on substrates, mainly in the roots of mangroves (4) . Mangrove oysters are produced using artisanal techniques, which include the sampling of naturally settled spats at different places in an estuary (3) .…”
Section: Introductionmentioning
confidence: 99%
“…No Brasil, a produção de moluscos bivalves é significativa nos Estados de Santa Catarina, Espírito Santo e São Paulo (RISTORI et al, 2007). No ano de 2015, o Estado de Santa Catarina teve uma produção de 17.000 toneladas de mexilhões e 3.000 toneladas de ostras (SCARDUA et al, 2017), representando quase o total da produção nacional. No entanto, nas regiões Sudeste e Sul, foi observado um incremento de 19% e 21% na produção de moluscos, respectivamente.…”
Section: Aspectos Da Produção De Consumo De Pescadounclassified